The Tomb of Doda Baba at Nawagai in the Light of Fresh Evidence - Rahman, Lutf-ur (Ancient Pakistan, 2016)
Doda Baba’s tomb is situated in Nawagae, Bajaur Agency. Owing to lack of historical and inscriptional evidence, Doda Baba was an unknown person. However, a couple of inscription have been discovered, related to ‘Doda Baba’, which has thrown sufficient light on the identity of the saint.